Challenges Facing the International Criminal in Trying to Accomplish its Mission Focusing on Omar Al Bashir’s Prosecution - Sakarombe, Emmanuel (International Journal of Law and Public Policy (IJLAPP), 2023)
The prosecution of former Sudanese President Omar Al Bashir has attracted great attention in the legal and academic spheres. At the center of the debate are pertinent issues surrounding the challenges and prospects that the International Criminal Court (ICC) is facing in prosecuting former Sudanese President Omar Al Bashir for crimes against humanity and war crimes. Ideally, a leader of a country should be arrested if he or she commits international crimes. However, in the case of Sudan and former President Al Bashir, it was difficult to get cooperation from the government. This article will unpack the role of the ICC in dealing with crimes against humanity and war crimes in Sudan committed by Al Bashir. This research relies documentary search/desk research. The major finding of this study include that there is a legal basis for the presence of ICC in Sudan since the Sudanese case was referred to the ICC by the United Nations Security Council (UNSC). The researcher discovered that the ICC faced a lot of hurdles in exercising its mandate and roles in prosecuting former Sudanese President Al Bashir, one the major challenge was the issue of non-cooperation by the African Union (AU) and African states, this is a challenge because the ICC relies on state cooperation to arrest Al Bashir. Another relevant finding is that there are prospects that Al Bashir will be arrested, this is due to unfolding events in Sudan. The researcher discovered that the new military government in Sudan, is showing signs of cooperation which would likely affect some African countries and the AU to cooperate with the ICC in arresting Al Bashir and surrendering him for trial in the ICC. In line with the conclusion, this study recommends that African states and the AU should consider contributing and cooperating with the ICC so that it can effectively operate in prosecuting perpetrators of international crimes.